Media Pembelajaran Pengenalan Huruf dan Angka dengan Teknologi Augmented Reality Berbasis Mobile Pada TK Islam Insan Permata - Viar Arya Dhita; Rita Wahyuni Arifin (Bandung Conference Series: Mathematics, 2022)
Abstract. The development of language skills for children is very important, namely as a means of communication or connecting themselves in society later. This ability looks simple but is very important to master for early childhood, especially in Insan Permata Islamic Kindergarten. Because it makes the initial capital to have reading skills. In addition to the ability to recognize letters, Insan Permata Islamic Kindergarten children also need to recognize numbers as a basis for learning to count. Learning methods for children under the age of 6 (six) years tend to be conventional based on books and instructions from teacher staff (teaching staff) so that the learning process for recognizing letters and numbers lacks interactive media to attract children's enthusiasm and learning methods with books confuse children - children in recognizing letters and numbers. Seeing these problems, this final project will develop an application with mobile-based Augmented Reality technology that can help learning activities. In the design, the 4-D version of the multimedia development method is used with the following stages: Definition, Design, Development and Dissemination. This research has produced a mobile-based letter and number recognition learning media application to help early childhood know technology and attract the enthusiasm of children, especially Insan Permata Islamic Kindergarten students. Abstrak. Pengembangan kemampuan bahasa bagi anak sangat penting yaitu sebagai alat komunikasi atau menghubungkan dirinya di masyarakat nanti. Kemampuan ini terlihat sederhana namun sangat penting untuk dikuasai bagi anak – anak usia dini khususnya pada TK Islam Insan Permata. Karena menjadikan modal awal untuk memiliki keterampilan membaca. Selain kemampuan pengenalan huruf, anak - anak TK Islam Insan Permata juga perlu untuk mengenali angka sebagai dasar untuk belajar menghitung. Metode belajar pada anak usia dibawah 6 (enam) tahun cenderung bersifat konvensional berdasarkan buku dan instruksi dari staf guru (tenaga pengajar) sehingga proses belajar pengenalan huruf dan angka kurang adanya media interaktif untuk memikat antusiasme anak – anak dan metode pembelajaran dengan buku membingungkan anak – anak dalam pengenalan huruf dan angka. Melihat permasalahan tersebut, pada tugas akhir ini akan dikembangkan sebuah aplikasi dengan teknologi Augmented Reality berbasis mobile yang dapat membantu kegiatan pembelajaran. Pada perancangan digunakan metode pengembangan multimedia versi 4-D dengan tahapan: Pendefinisian (Define), Perancangan (Design), Pengembangan (Develop) dan Penyebaran (Disseminate). Dalam penelitian ini telah menghasilkan aplikasi media pembelajaran pengenalan huruf dan angka berbasis mobile untuk membantu anak - anak usia dini mengetahui teknologi dan menarik antusiasme anak - anak khususnya para murid TK Islam Insan Permata.